Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.12659/msm.899214
|View full text |Cite
|
Sign up to set email alerts
|

Induction of K562 Cell Apoptosis by As4S4 via Down-Regulating miR181

Abstract: BackgroundChronic myelogenous leukemia (CML) has unsatisfactory treatment efficacy at present. As the major component of red orpiment, tetra-arsenic tetra-sulfide (As4S4) has been recently used in treating leukemia, but with unclear mechanism targeting CML. MicroRNA (miR) is a group of endogenous non-coding RNAs regulating pathogenesis. MiR181 has been shown to exert important roles in tumor progression. The relationship between miR181 and As4S4 in inducing K562 cell apoptosis, however, is still unclear.Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…11,23 Moreover, As 4 S 4 facilitates CML cell apoptosis through downregulating miR-181 as well as Bcl-2 expressions and promoting apoptotic protein Caspase-3 activity. 24 These studies emphasized the antiproliferative or proapoptotic function of As 4 S 4 in APL as well as CML, and we speculated that As 4 S 4 might also have good antitumor effect in other hematological malignancies, especially MM, while the effect of As 4 S 4 on MM cells was rarely reported. Thus, to investigate whether As 4 S 4 had killing effect on MM cells, we treated U266 cells with different concentrations of As 4 S 4 , and we found that As 4 S 4 repressed cell viability in a dose-/time-dependent manner in U266 cells, which may be due to (1) As 4 S 4 might induce MM cell apoptosis via promoting proapoptotic factor (such as PP2A) or inhibiting antiapoptotic factor (such as Bcl-2), thereby reduced MM cell viability; 11,24 (2) As 4 S 4 might regulate some downstream signaling pathways to decrease the cell viability, such as its downstream JAK2/STAT3 signaling pathway, which was displayed in our results.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…11,23 Moreover, As 4 S 4 facilitates CML cell apoptosis through downregulating miR-181 as well as Bcl-2 expressions and promoting apoptotic protein Caspase-3 activity. 24 These studies emphasized the antiproliferative or proapoptotic function of As 4 S 4 in APL as well as CML, and we speculated that As 4 S 4 might also have good antitumor effect in other hematological malignancies, especially MM, while the effect of As 4 S 4 on MM cells was rarely reported. Thus, to investigate whether As 4 S 4 had killing effect on MM cells, we treated U266 cells with different concentrations of As 4 S 4 , and we found that As 4 S 4 repressed cell viability in a dose-/time-dependent manner in U266 cells, which may be due to (1) As 4 S 4 might induce MM cell apoptosis via promoting proapoptotic factor (such as PP2A) or inhibiting antiapoptotic factor (such as Bcl-2), thereby reduced MM cell viability; 11,24 (2) As 4 S 4 might regulate some downstream signaling pathways to decrease the cell viability, such as its downstream JAK2/STAT3 signaling pathway, which was displayed in our results.…”
Section: Discussionmentioning
confidence: 86%
“…Although the mechanisms of As 4 S 4 in solid tumors have been frequently explored, the current evidence about the mechanism of As 4 S 4 in hematological malignancies is mainly restricted to APL and CML. [22][23][24] For example, a previous study shows that As 4 S 4 inhibits cell proliferation and induces cell apoptosis via blocking the cell cycle in the S and G2/M phases in APL cells. 22 Besides, studies show that As 4 S 4 downregulates SET protein expression and further promotes the proapoptotic factor protein phosphatase 2A (PP2A) expression to enhance cell apoptosis and represses cell proliferation in a dose-/timedependent manner in APL cells.…”
Section: Discussionmentioning
confidence: 99%
“…Inducing apoptosis of human liver cancer HepG2, QGY-7703 cells and blocking cell cycle G2/M progression [ 134 137 ]…”
Section: Introductionmentioning
confidence: 99%